NEW FTIR METHOD DEVELOPMENT AND VALIDATION FOR QUANTITATIVE ANALYSIS OF FAVIPIRAVIR IN BULK AND PHARMACEUTICAL DOSAGE FORMS - P., NITHILA; RAGHAVENDRABABU, N.; PADMAVATHI, Y.; NEENA, G.; SUSHMA, K.; POOJITHA, A. (International Journal of Current Pharmaceutical Research, 2022)
Objective: A simple spectrophotometric method has been proposed for quantitative analysis of favipiravir in bulk and pharmaceutical dosage form. Methods: New Fourier transform infrared (FTIR) spectroscopic method has been developed for the estimation of favipiravir by using solid pellet technique. Results: Results were linear over the 20–100µg/mg concentration range, with correlation values exceeding 0.999. The approach was thoroughly validated in accordance with the recommendations of the International Conference on Harmonization, demonstrating acceptable levels of accuracy, precision, selectivity, robustness, and linearity. Conclusion: The statistical comparison between this method and HPLC revealed that the newly developed method was significantly distinct. Thus, it proves to be applicable. It met all validation standards over a variety of concentrations and can be used as a substitute for the official procedures.